OFR-19-83 Contamination Of Ground And Surface Waters By Uranium Mining And Milling - Volume II. Field Sampling And Empirical Modeling - Gergely Markos (The National Institute for Occupational Safety and Health (NIOSH), 1981)
Uranium mill tailings represent a potential threat to the human habitat by containing large amounts of radioactive and chemically toxic substances in high concentrations. These: undesired components enter the human habitat in various pathways such as by erosion and water or air transport. The main objective of this investigation was to evaluate the actual movement and model the potential movement of contaminants by seepage of water from the tailings into the subtailings soil. This report represents various models of the movement of contaminants using both theoretical approaches and empirical evaluation of data available from other investigations. The data consist of field measurements and laboratory determi¬nations of major and trace cations, the dominant anions, pH, and Eh of moist solids, extracts, and waters from the tailings and surroundings. Evaluation and interpre¬tation of data were accomplished by using Eh-pH diagrams, various statistical methods and the WATEQFC computer program. Data analyses show that the critical area of investigating movement- is the interfaces between tailings and the external environment. The chemical differences at interfaces seem to result in a sink system for contaminants. The tailings-soil¬-water system shows extreme complexities because of chemical and physical hetero¬geneity of the system preventing the use of a single comprehensive model to represent real conditions. The validity of the simplifying assumption used has been shown and increasing complexity has been built into the models. Analogs of these models can be used for evaluation of similar systems.